Prediction of Random Vibration Fatigue Damage Using Isogeometric Modelling - Wang, Shubiao; Khalij, Leila; Troian, Renata; Shi, Lujie (Computer Assisted Methods in Engineering and Science, 2021)
The finite element analysis (FEA) method is indispensable in simulation technology, as it can help engineers predict results to avoid the cost of experimental testing. However, the finite element mesh generation process can be time-consuming, and the approximate mesh model can lead to inaccurate stress results. Improving the accuracy of stress estimation leads to a better assessment of damage or life of mechanical components. In this study, we applied the isogeometric analysis (IGA) implemented in LS-DYNA software to study two specimens subjreted to the stationary Gaussian random loads. These geometric models were represented by non-uniform rational B-spline (NURBS) to assess the damage and fatigue life in the frequency domain by using Dirlik’s distribution and cumulative damage. A comparison with FEA was conducted to highlight the main differences. Experimental fatigue tests with an electrodynamic shaker were also carried out to check if the fatigue lives predicted by numerical models are consistent. The study showed that IGA predicts similar results to FEA with an acceptable relative error and reduced the time for mesh generation, requiring fewer integration points and mesh elements.